Microbial Quality of Paddy fields at Alfurat Alawsat Area, Iraq and the Effect of Milling Process on the Rice Contamination Level - Abeer S. Alhendi; Aqeel M. Ali; Abeer K. Mohammed (Baghdad Science Journal, 2023)
Fifty-Four paddy samples, 45 soil samples, and nine irrigation water samples of some paddy fields at Alfurat Alawsat Area, Iraq were collected to investigate the microbial quality including total count bacteria (TCB), molds and yeast, total coliform (TC), and E. coli bacteria. Paddy samples were processed at the laboratory level to produce rice at 32 and 36 whiteness, and the microbial quality of the produced rice was conducted too. The results showed that all irrigation water samples were overpassed the FDA limit for E. coli. All paddy samples were exceeded the good limit of TCB, but no sample exceeded the acceptable limit. Most paddy samples were exceeded the FDA limit for molds and yeast, and few paddy samples exceeded the total coliform limit. The milling process reduced microbial levels for some samples, while the effect was undetectable for other samples. Ten rice samples at 32 whiteness and eight rice samples at 36 whiteness out of 13 paddy samples overpassed FDA and Iraqi Quality Standardization (IQS) for molds and yeast. All produced rice at both whiteness levels was exceeded the total coliform of IQS, while only six and three samples out of 13 rice samples at 32 and 36 whiteness respectively overpassed the FDA limit. In conclusion, paddy samples taken from Alfurat Alawsat fields were overpassed some microbial levels from fields without the effect of storage or milling processing. Irrigation water was probably the main source of fields’ contamination, therefore, the paddy fields need to be monitored and controlled in terms of their microbial contamination.